(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2026)
Background: Tourism enterprises increasingly function in an environment where economic performance is balanced with environmental responsibility and social equity. Social value creation emerged as a key mechanism through which tourism enterprises contribute to sustainable development. Objective: Illustrating the application of Stakeholder Theory and the United Nations Sustainable Development Goals (SDGs), this study examines the influence of Social Value Creation (SVC) on Sustainable Tourism Outcomes (STO), with Sustainable Business Models (SBM) and Community Empowerment (CE) as mediating mechanisms. Methodology: A total of 386 samples were collected using a structured questionnaire administered via online survey. The validated questionnaire has been taken and slightly modified to capture the respondents’ perceptions of social value creation practices, sustainable business model adoption, community empowerment initiatives and sustainable tourism outcomes. A non-probability, purposive sampling approach was adopted, ensuring the respondents had relevant experience in tourism enterprises with a social or sustainable orientation from the Tamil Nadu region of India. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study tests the conceptual framework empirically by linking social entrepreneurship and sustainability in tourism. Results: The findings demonstrate that social value creation significantly influences sustainable business models and community empowerment, thereby enhancing sustainable tourism outcomes. Community empowerment emerged as the most influential predictor of sustainability. The model explains a substantial proportion of the variance in sustainable tourism outcomes, thereby strengthening the central role of stakeholder-centric, SDG-aligned tourism development. Conclusion: This study examined the role of social entrepreneurship, where social value creation embedded within tourism social enterprises contributes to sustainable tourism outcomes and identified the mechanisms through which this relationship operates.